Sub-National Analysis of Systematic Differences in Health Status and the Access to and Funding of Health Services : An Example from Comoros - Haazen, Dominic S. (World Bank, Washington, DC, 2017)
This report analyzes the available data to determine if there are systemic differences in the access to and funding of health services in different sub-regions of Comoros, and to link these to variations in the socioeconomic status of residents in these sub-regions. It focuses on a number of key questions that are analyzed at the sub-national level, including: the effect of out-of-pocket payments on household financial well-being; whether out-of-pocket payments for health are progressive or regressive; whether ill health is more concentrated among the poor; whether the poor use health services less than the rich; and the major sources of financing for the health system in Comoros. It introduces a specific analysis of pockets of poverty - the five sub-regions with the highest level of poverty headcount (more than 50 percent) - comparing their characteristics to those of the remaining sub-regions. These pockets of poverty appear to have generally lower utilization of health services, poorer health outcomes in some areas (although not on aggregate measures which bears further analysis), and lower levels of health spending, especially from the public sector. Aside from the conclusions and potential policy implications for Comoros, it may be useful to apply this type of analysis in other countries.